(3GdJMdjd GdGbJUGOj GdLRFjs (3edNUGJ GdOQhS h JeGQjf eMdhdI (B: (3GdLRA GdChds - (3HhSYOI(B, (3SYjOIs; (3YjGT, hQjOIs; (3eNJGQ QMeGfj, McjeIs ((3GdLRGFQs (3OGQ gheIs, 2017)
(3ebOeI aj GdJMdjd GdGbJUGOj h GdeTcdI GdGbJUGOjI, GdWdH h GdYQV h GdJhGRf, bjGS GdehGRfGJ, JWHjbGJ Ydi JhGRf GdShb, JMdjd Sdhc GdeSJgdc(B/(3fXQjI GdefaYI,JMdjd Sdhc GdeSJgdc(B/(3fXQjI efMfjGJ GdShGA(B.s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdGbJUGO GdLRFjs